Pengaruh Berbagai Media Budidaya terhadap Performa Produksi Larva Maggot (Hermetia ilucens): The Effect of Using Different Cultivation Media For The Cultivation of Hermetia Ilucens Larvae - Nurina Rahmawati (Universitas Islam Negeri Alauddin Makassar, 2023)
Maggot has the potential as a feed mixture. In an effort to produce good Maggot, the best media is needed for the growth and reproduction of these larvae. The purpose of this study was to determine the effect of using different cultivation media for Black Soldier Fly Larvae (Hermetia ilucens) culture media. This research was conducted in Sidomulyo Village, Puncu District, Kediri Regency. This research method used a completely randomized design (CRD), which consisted of 4 treatments and 6 replications and each replication consisted of 0.5 grams of MAGGOT Larvae eggs, the study was carried out until the larvae were 28 days old. The treatment was arranged in the order P1 using food waste, P2 fruit and vegetable and fruit waste, P3 commercial feed and P4 chicken excreta. The observed variables were regarding the performance of Maggot larvae in the form of colony weight, larval weight, length and consumption of Maggot larvae. The results showed that there was no significant effect in each treatment on colony weight, larval weight, length and consumption of Maggot larvae. The average colony weight from lowest to highest was P4 (391), P2 (800), P1 (900), P3 (933) gram/colony. The average weight of Maggot larvae started from the lowest to the highest, namely P4 (45), P1 (71), P2 (94), P3 (94) mg/head. The average length from the lowest to the highest was P4 (4.43), P1 (9.63), P2 (10.1), and P3 (13.3) mm/head and the average consumption from the lowest to the highest P4 (1842), P2 (2150), P3 (2467), and P1 (2500) g/treatment for 28 days of study. The results of the study explained that commercial feed media gave the best results on colony weight, average weight and maggot length.